RESPON MEDIA TANAM DAN PEMBERIAN AUKSIN ASAM ASETAT NAFTALEN PADA PEMBIBITAN AREN (Arenga pinnata Merr) - Utri Patma1 Utri Patma1; Lollie Agustina P. Putri Lollie Agustina P. Putri Lollie Agustina P. Putri; Luthfi A Mahmud Siregar (Universitas Sumatera Utara, 2013)
ABSTRACT Growth of plant is affected by some factors; among other things are plant media and auxin application. A research had been conducted at Pasar II Setiabudi, Kelurahan Tanjung Sari, Medan (± 25 m asl) in March – August 2012. The objective of the research was to know response of plant media and auxin naphtalene acetic acid application on the growth of sugar palm seed. The research that use Randomized Block Design with two factor that plant media of (top soil + sand + compost), (top soil + husk charcoal + compost), (top soil + sand + husk charcoal + compost) and auxin application were of 0 ppm, 50 ppm, 100 ppm and 150 ppm. The parameters observed were increase seed height, leaf sum, leaf klorofil and steam diameter. The result of research showed that the response plant media and auxin naphtalene acetic acid application on sugar palm nursery with interaction between plant media and auxsin application were not significantly to all the parameters observed. Keywords : plant media, auxsin application, sugar palm